Critical Storytelling Experiences of Power Abuse in Academia - Hansen, Julie; Nilsson, Ingela (Brill, 2022)
What does power abuse look and feel like in the academic world? How does it affect university faculty, students, education and research? What can we do to counteract and prevent power abuse? These questions are addressed in this collection of autobiographical poems, essays and illustrations about academia. The contributors reflect on individual experiences as well as underlying institutional structures, providing original perspectives on bullying, sexual harassment, discrimination, and other forms of power abuse in academic workplaces. They share their stories in order to break the culture of silence around power abuse in academia and point out pathways for constructive change.